Integrasi Kurikulum Sekolah Dan Pendidikan Kewarganegaraan dalam Mencegah Sikap Intoleransi Pada Peserta Didik Era Post-truth - Yulius Rustan Effendi; Didik Iswahyudi; Elisabeth Djo Io Wea (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the integration of Citizenship Education in the school curriculum as a prevention strategy of intolerance of students in the post-truth era, with a case study in the Santa Maria II Catholic Middle School, Malang. The post-truth Era, which is full of hoaxes and disinformation through digital media, has the potential to form intolerant attitudes, so Citizenship Education has an important role in equipping students with the value of tolerance and critical thinking skills. This study uses a qualitative approach through in-depth interviews and participatory observation to explore the implementation of the curriculum and the role of teachers. The results showed that the integration of civic values in formal curricula and non-formal activities, such as extracurriculars and character strengthening programs, effectively shaped students ' tolerant attitudes. The implementation of independent curriculum and digital literacy also strengthens students ' resilience to disinformation. Teachers play a central role as facilitators in developing critical thinking skills. The study recommends a holistic approach involving cognitive, affective, and psychomotor aspects, as well as collaboration between schools, parents, and the community. In conclusion, contextual and interdisciplinary integration of civic education in the school curriculum proved effective in preventing intolerance among learners.